(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nusupov AM, Sambetbaev AA, Kozhebaev BZ, Nurzhanova KH, Gorelik OV. 2021. A comparison of the milk yield and morphometrics of Irtysh type Simmental cows and their Holstein and Simmental crosses in East Kazakhstan. Biodiversitas 22: 3663-3670. Cattle breeding is still a significant part of agriculture manufacture both in milk and beef production. Dairy manufacture needs more and more modifications to increase milk productivity and produce milk with better nutrition properties. The authors present a comparison of the dairy cattle of the Simmental breed (Kazakhstan Irtysh type) and its cross-breeds with red-piebald Holstein and Simmental breeds. All the animals’ breeds were studied at the time of the first lactation period in cows at the “Kamyshinskoye” farm, Shemonaikha District, East Kazakhstan region. We studied the milk productivity, exterior parameters, and reproductive indicators for the control animal group (Simmental breed Irtysh type) and the crosses (cross-breeds) of the red-piebald Holstein when collecting the research results and Irtysh type and Simmental and Irtysh type. All data obtained in this study have been fully compared with the indicators of the first lactation period of Simmental cows of the Irtysh type. As a result of the study, authors have created the curve of the 305-day lactation period, studied the exterior of the animals, the morphological structures of the udder, and the annual capacity cycles of the tested cows’ group. The milk yield obtained in the first complete lactation period from the red-piebald Holstein cross-animals was 240 kg or 4.2% more than the control mother group, but the average milk fat percentage has been 0.09% less. On the contrary, the cross of the Irtysh and Simmental breed has a yield less by 258 kg or 4.7% (5277 kg), but a fat milk percentage has been 0.1% more.